Incidence and Predictors of Cancer Following Kidney Transplantation in Childhood. Issue 10 (8th May 2017) - Francis, A.; Johnson, D. W.; Craig, J. C.; Wong, G.
Abstract : Cancer risk is increased substantially in adult kidney transplant recipients, but the long‐term risk of cancer in childhood recipients is unclear. Using the Australian and New Zealand Dialysis and Transplant Registry, the authors compared overall and site‐specific incidences of cancer after transplantation in childhood recipients with population‐based data by using standardized incidence ratios (SIRs). Among 1734 childhood recipients (median age 14 years, 57% male, 85% white), 289 (16.7%) developed cancer (196 nonmelanoma skin cancers, 143 nonskin cancers) over a median follow‐up of 13.4 years. The 25‐year cumulative incidences of any cancer were 27% (95% confidence intervals 24–30%), 20% (17–23%) for nonmelanoma skin cancer, and 14% (12–17%) for nonskin cancer (including melanoma). The SIR for nonskin cancer was 8.23 (95% CI 6.92–9.73), with the highest risk for posttransplant lymphoproliferative disease (SIR 45.80, 95% CI 32.71–62.44) and cervical cancer (29.4, 95% CI 17.5–46.5). Increasing age at transplantation (adjusted hazard ratio [aHR] per year 1.10, 95% CI 1.06–1.14), white race (aHR 3.36, 95% CI 1.61–6.79), and having a functioning transplant (aHR 2.27, 95% CI 1.47–3.71) were risk factors for cancer. Cancer risk, particularly for virus‐related cancers, is increased substantially after kidney transplantation during childhood. Abstract : ANZDATA registry data suggest that after childhood kidney transplantation, cancer risk increases by eightfold compared to the general population, with 30‐ to 45‐fold increased risk for viral‐related cancers, and predictors for increased risk include increasing age, white race, and a functioning transplant.